Split‐dose bowel preparation with polyethylene glycol for colonoscopy performed under propofol sedation. Is there an optimal timing?. Issue 3 (March 2017) - Alghamry, Alaa; Ponnuswamy, Sureshkumar K; Agarwal, Aditya; Moattar, Hadi; Yerkovich, Stephanie T; Vandeleur, Ann E; ,; Thomas, James; Croese, John; Rahman, Tony; Hodgson, Ruth
Abstract : OBJECTIVE: Aspiration risk, especially with propofol sedation, remains a concern after split‐dose bowel preparation of up to 1 L polyethylene glycol for the procedure. We aimed to identify the ideal timing of bowel preparation to achieve optimal colon cleansing with no increased risk of aspiration. METHODS: A total of 892 consecutive patients undergoing simultaneous esophagogastroduodenoscopy (EGD) and colonoscopy were prospectively recruited. Residual gastric volume (RGV) and pH of gastric contents were measured at EGD, and patients' characteristics, runway time (duration between completion of the final liter of bowel preparation and colonoscopy commencement), and cleansing quality were recorded. RESULTS: A shorter runway time resulted in better colon cleansing ( r = −0.124, P < 0.001). No correlation between runway time and RGV or pH was found ( r = −0.017, P = 0.62 and r = −0.030, P = 0.47, respectively). RGV and pH did not differ significantly with runway time of 4 or 5 h. RGV with runway time ≤3 h was 35.9 ± 11.8 mL and 17.4 ± 0.6 mL after runway time >3 h ( P < 0.001). No aspiration pneumonia occurred. The only factors independently related to higher RGV were younger age and male sex. CONCLUSIONS: The consumption of bowel preparation agent within 3–4 h before propofol sedation resulted in a similar RGV and pH as those achieved by more prolonged fasting, with no increased risk of aspiration even in patients perceived to be at high risk.